DIGITAL BRANDING TRAINING TO IMPROVE PRODUCTION ACTIVITIES IN THE START-UP BUSINESS SECTOR - Ramdan, Ahmad Taufiq Maulana; Tawaqal, Rizki Surya (Universitas INABA, 2022)
The impact of the global crisis is starting to be seen at the national level due to the rapid spread of Covid-19. The COVID-19 epidemic has had a profound impact on the business sector, including micro, small and medium enterprises. Many business actors have laid off their employees and even temporarily closed their business activities. Given the circumstances and events mentioned above, it is very important for new business actors to continue to maintain consumer loyalty, with Brands playing the most significant role. The problem with today's entrepreneurs is that they continue to lack a fundamental understanding of brands. Beginning entrepreneurs are aware that brands are nothing more than logos and packaging. Another problem is that inexperienced business people do not know how to take advantage of the current digital era to activate brands in the minds of consumers. Start-up business players should exercise adequate branding to protect their trademarks from infringement and imitation by other commercial entities.